2020
DOI: 10.3390/catal10030276
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication-Assisted Synthesis of ZnxCd1−xS for Enhanced Visible-Light Photocatalytic Activity

Abstract: Zn x Cd 1−x S as a solid solution photocatalyst has attracted widespread attention for its unique adjustable band gap structure and good and stable performance. A novel synthesis approach for Zn x Cd 1−x S is still required to further improve its performance. In this study, we synthesized a series of Zn x Cd 1−x S (x = 0−1) solid solutions via an ultrasonication-assisted hydrothermal route. In comparison with conventional methods of preparation, the sample prepared by our innovative method showed enhanced phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The Au doped Cd 0.25 Zn 0.75 S nanostructures had exhibited 97% of photo-catalytic removal capacity of MB dye which is 20% superior to the Cd 0.25 Zn 0.75 S nanostructures [41]. Zn 0.3 Cd 0.7 S exhibited the maximum level of photo-catalytic activity and stability for the degradation of MO with k = 0.85 h −1 , which is 2.2 times higher than that of CdS [42]. The optical properties of the Zn added CdS revealed that the energy gap of Zn-doped CdS is higher than the energy gap of the pure CdS nanostructures [43].…”
Section: Introductionmentioning
confidence: 95%
“…The Au doped Cd 0.25 Zn 0.75 S nanostructures had exhibited 97% of photo-catalytic removal capacity of MB dye which is 20% superior to the Cd 0.25 Zn 0.75 S nanostructures [41]. Zn 0.3 Cd 0.7 S exhibited the maximum level of photo-catalytic activity and stability for the degradation of MO with k = 0.85 h −1 , which is 2.2 times higher than that of CdS [42]. The optical properties of the Zn added CdS revealed that the energy gap of Zn-doped CdS is higher than the energy gap of the pure CdS nanostructures [43].…”
Section: Introductionmentioning
confidence: 95%
“…Zn x Cd 1−x S has attracted widespread interest as a solid solution photocatalyst due to its unique adjustable band-gap structure and its good stable performance. A series of ZCSs with nanosheet structures were successfully synthesized by an ultrasonication-assisted hydrothermal method [10]. All solid solutions (except for x = 0.8−1.0) showed greater efficiency to photocatalytically degrade MO solution under visible light in comparison to CdS.…”
mentioning
confidence: 99%
“…The balance between band-gap structure-directed redox capacity and light absorption of Zn 0.3 Cd 0.7 S accounts for its good photocatalytic performance. In this way, Yang et al [10] contributed a novel strategy to synthesize highly efficient sulfide photocatalysts.…”
mentioning
confidence: 99%